2009
DOI: 10.17221/963-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Olive Oils during Microwave and Conventional Heating for Fast Food Preparation

Abstract: Abstract:The oxidation stability of extra virgin and refined olive oils produced in different countries were studied under different conditions of microwave heating (microwave oven Electrolux, 2450 MHz, 500 W) and conventional heating (200°C). Oils were heated in a microwave oven and in a conventional oven for 0, 3, 6, 9, 12, 15, 20, 25, and 30 minutes. The evaluated parameters were peroxide value, content of conjugated dienes, conjugated trienes (determined by absorbance at 233 nm and 274 nm, respectively), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Different experimental techniques, including gas chromatography, nuclear magnetic resonance Raman spectroscopy and fluorescence spectroscopy have been previously employed to characterize EVOO and other edible oils to investigate adulteration, heating effects and quality [15,18,19,22,[25][26][27][28][29][30][31][32][33]. Of these techniques, fluorescence spectr oscopy is less time consuming, simple in operation and analysis, cost effective, quick and reliable for the characterization of edible oils [15-18, 21, 31, 32, 34-36] and it needs no sample preparation.…”
Section: Laser Physicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different experimental techniques, including gas chromatography, nuclear magnetic resonance Raman spectroscopy and fluorescence spectroscopy have been previously employed to characterize EVOO and other edible oils to investigate adulteration, heating effects and quality [15,18,19,22,[25][26][27][28][29][30][31][32][33]. Of these techniques, fluorescence spectr oscopy is less time consuming, simple in operation and analysis, cost effective, quick and reliable for the characterization of edible oils [15-18, 21, 31, 32, 34-36] and it needs no sample preparation.…”
Section: Laser Physicsmentioning
confidence: 99%
“…In the fourth experiment, EVOO samples were heated at 150 °C in an electrical oven for a period of 5, 10, 20 and 30 min respectively. This was actually done to observe the spectral changes induced in the EVOO molecular composition as a result of cooking at a temperature of 150 °C for a longer period of time, which is normally 5 − 30 min in household cooking [25]. The above-mentioned cooking range is found for frying purposes; however, if a pressure cooker were used, then 121 °C is the maximum cooking temperature which is achieved in a commercial cooker.…”
Section: Sample Preparationmentioning
confidence: 99%
“…As different food items need different times for frying or cooking, normally 5–30 min are proposed for domestic cooking. 9 Therefore, cooking with Desi ghee for longer heating times has been investigated in the present study. Figure 7a shows Raman spectra from all these samples whereas the PCA scatter plot is displayed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is important to investigate temperature effects on Desi ghee to enjoy the real benefits of their ingredients. The effects of temperature on edible oils have been investigated by many authors, [5][6][7][8][9][10][11][12][13] but no-one has reported the temperature effects on the molecular composition of Desi ghee. For extra virgin olive oil (EVOO), a temperature of 190 C has been suggested, where variations in its molecular composition does not change much.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in the context of cooking, a variety of chemical changes are expected to occur depending on the nature of technique as well as the degree of heating and exposure time.These changes include chemical reactions, which in turn can be in the form hydrolysis, oxidation and polymerization all of which lead to possible loss of nutritional values and in some cases at long run causes a serious health problem due to release of free radicals namely cancer. Indeed, it has been shown[21] that microwave cooking of fatty foods at high temperature produces isomeration (i.e., formation of trans) of the double bonds of fatty acids. In a research,[22] used…”
mentioning
confidence: 99%